Exploring Key Correlates of Trail Satisfaction and their Nonlinear Relationships in Suburban Areas - Jasmine Cao; Chun Yin (Findings)
Using data collected from trail users in Woodbury, MN, this study applies gradient-boosting decision trees to explore the nonlinear associations between trail elements and user overall satisfaction. Scenery, personal safety, and connection are the most important contributors to overall satisfaction. Several trail elements show nonlinear effects on overall satisfaction. Specifically, bumps and lighting greatly affect overall satisfaction when their performance is poor, whereas personal safety, home access to trails, and shade improve overall satisfaction when performing well. The results also showed that the city should prioritize improvements on bumps, lighting, roadway crossing, safety, and access to enhance user satisfaction effectively.